Genetically determined plasma trefoil factor-3 levels are causally associated with the risk of ulcerative colitis: a Mendelian randomization study - Toraman, Bayram; Fidan, Sami; Yıldız, Gökhan (The European Research Journal, 2024)
Objectives: Ulcerative colitis (UC) is an inflammatory disease restricted to the colon’s mucosal layer. UC is a complex disease with a largely unknown etiology. Mendelian Randomization (MR) is a method that uses variations in genes that have a causal effect of a modifiable exposure to the disease, in genetic epidemiological studies. Trefoil factor 3 (TFF3) is a secreted protein expressed mainly in the colonic mucosa that binds with the mucin 2 protein, forming a protective barrier for the colon mucosa from bacteria and other insults. This study aimed to identify if TFF3 levels in plasma are causally associated with UC. Methods: We performed a two-sample MR study. For exposure instrumental variables (IVs), genetically determined TFF3 levels in plasma proteome quantitative trait locus data were obtained from the published literature. Outcome data were obtained from the GWAS catalog. The “TwoSampleMR” R package was used for MR. The statistical significance of IV effect sizes on the outcome is mainly evaluated by the inverse variance weighted (IVW) method. Results: The IVW test showed considerable statistical significance in all analyzed outcomes except for Crohn’s disease (CD) samples. Heterogeneity and horizontal pleiotropy tests showed no significant results for MR sensitivity analysis. Conclusions: We showed that TFF3 levels in plasma were causally associated with the risk of UC. Increased levels of TFF3 are reversely associated with the risk of UC. The absence of any causal relationship between TFF3 and CD from the same study cohort also supports our causal inference.